2021
DOI: 10.3390/ijms222111826
|View full text |Cite
|
Sign up to set email alerts
|

Why Have the Benefits of DHA Not Been Borne Out in the Treatment and Prevention of Alzheimer’s Disease? A Narrative Review Focused on DHA Metabolism and Adipose Tissue

Abstract: Docosahexaenoic acid (DHA), an omega-3 fatty acid rich in seafood, is linked to Alzheimer’s Disease via strong epidemiological and pre-clinical evidence, yet fish oil or other DHA supplementation has not consistently shown benefit to the prevention or treatment of Alzheimer’s Disease. Furthermore, autopsy studies of Alzheimer’s Disease brain show variable DHA status, demonstrating that the relationship between DHA and neurodegeneration is complex and not fully understood. Recently, it has been suggested that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 228 publications
(335 reference statements)
0
6
0
Order By: Relevance
“…DHA supplementation has shown inconclusive results of both positive and negative effects related to BBB integrity [ 59 ] and improvement in AD symptoms [ 60 ]. This may be due to the inhibitory effects of DHA on ALA metabolism [ 55 ] and the lower formation of intermediate n-3 FA like EPA, also needed for membrane phospholipids building.…”
Section: Fatty Acid Metabolismmentioning
confidence: 99%
“…DHA supplementation has shown inconclusive results of both positive and negative effects related to BBB integrity [ 59 ] and improvement in AD symptoms [ 60 ]. This may be due to the inhibitory effects of DHA on ALA metabolism [ 55 ] and the lower formation of intermediate n-3 FA like EPA, also needed for membrane phospholipids building.…”
Section: Fatty Acid Metabolismmentioning
confidence: 99%
“…Second, whether supplementation with omega‐3 FA can improve AD has not yet been determined. Some evidence currently suggests that it is only effective in mild AD, some experiments show that supplementation with omega‐3 FA does not have a significant effect, and some literature even shows that DHA does not work at all 77 . However, the use of omega‐3 FA for therapeutic purposes is now mostly in animal experiments and less in clinical trials.…”
Section: Summary and Prospectmentioning
confidence: 99%
“…For example, Colombo et al found that prenatal DHA may positively affect infants’ attention and regulation [ 21 ], whereas Gould et al observed no benefit of prenatal DHA supplementation on child behavior; on the contrary, the results of Gould et al suggest an adverse effect of DHA on behavioral functioning [ 22 ]. Clarifying the mechanism of action of DHA can help guide supplementation during pregnancy [ 23 ].…”
Section: Introductionmentioning
confidence: 99%